2019
DOI: 10.1177/1753193419850116
|View full text |Cite
|
Sign up to set email alerts
|

Ulnar head replacement and sigmoid notch resurfacing arthroplasty with minimum 12-month follow-up

Abstract: Our study aimed to report the short-term outcomes of patients who underwent partial ulnar head replacement and distal radial ulnar joint interposition arthroplasty. From 2012 to 2016, nine patients underwent this procedure with mean follow-up of 27 months (range 12–55). Seven of the nine patients had previously undergone surgical intervention on the ipsilateral wrist. The procedure resulted in substantial improvements in pain and function. Mayo Wrist Score improved from 37 preoperatively to 73 postoperatively,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…The current review demonstrates an increase in number and percentage of reported LOE in the J Hand Surg Eur publications. Among these publications with LOE declaration in the European journal, many are American authors (Boe et al., 2018; Clark et al., 2019a, 2019b, Kazmers et al., 2019; Lovy et al., 2019; Trehan et al., 2019). It is clear that it is not American authors who have resistance or difficulty in declaration of LOE.…”
Section: Discussionmentioning
confidence: 99%
“…The current review demonstrates an increase in number and percentage of reported LOE in the J Hand Surg Eur publications. Among these publications with LOE declaration in the European journal, many are American authors (Boe et al., 2018; Clark et al., 2019a, 2019b, Kazmers et al., 2019; Lovy et al., 2019; Trehan et al., 2019). It is clear that it is not American authors who have resistance or difficulty in declaration of LOE.…”
Section: Discussionmentioning
confidence: 99%